Non-sterile substrate cultivation of oyster mushrooms on fresh Giant Juncao Grass: a scalable strategy for sustainable nutrition in underdeveloped regions - Zhang, Yulong; Lu, Yiting; Li, Zhijun; Xie, Mingjun; Wen, Fengmei; Li, Jing; Rensing, Christopher; Azam, Syed Muhammad; Chen, Jingsi; Luo, Lin; Yan, Fan; Okal, Eyalira Jacob; et al. (Frontiers in Sustainable Food Systems, 2025)
Malnutrition in underdeveloped regions is exacerbated by the lack of accessible, nutrient-dense foods and energy-intensive agricultural practices. This study introduces a sustainable non-sterile cultivation method for Pleurotus sapidus (an oyster mushroom species) using fresh Pennisetum giganteum (Giant Juncao grass), a fast-growing C4 grass cultivated on marginal soils. Unlike conventional sterilization-dependent approaches, our method employs lime-saturated water (LW, 4 mL·g−1) to pretreat fresh grass, eliminating the need for drying; a critical advantage in humid regions where biomass degradation occurs rapidly. Coupled with optimized substrate composition (2% CaO, 0.5% corn flour), this strategy achieved robust mycelial growth (0.53 cm·d−1) and high biological efficiency (112.78%). LW treatment altered substrate metabolites and reduced soluble nutrients. L-malic acid and soluble sugars promoted P. sapidus growth, whereas amino acids, available nitrogen (N), phosphorus (P) and potassium (K), and lactic acid inhibited its growth. The Mucor circinelloides was identified as a key contaminant. This scalable strategy transforms underutilized lignocellulosic biomass into nutrient-rich food, aligning with SDG 2 (Zero Hunger) and SDG 12 (Responsible Consumption and Production).